2010
DOI: 10.1007/s11670-010-0093-9
|View full text |Cite
|
Sign up to set email alerts
|

Mutated genes in pancreatic cancer

Abstract: Pancreatic cancer continues to be a deadly malignancy with still high mortality and poor survival. Little progress has been made on the treatment of advanced pancreatic cancer despite the significant advances in understanding, diagnosis, and access to conventional and novel treatments. Molecular pathology of the lesion is the key of our understanding of the mechanisms underlying the development of this cancer and will probably help us in earlier diagnosis and better therapeutic results. New treatment strategie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Pancreatic cancer is often difficult to diagnose in the early stages; only 10–15% of patients are eligible for surgical treatment at diagnosis. Current clinical treatments for pancreatic cancer have limited efficacy, highlighting the need for improved treatment strategies to prolong patient survival [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic cancer is often difficult to diagnose in the early stages; only 10–15% of patients are eligible for surgical treatment at diagnosis. Current clinical treatments for pancreatic cancer have limited efficacy, highlighting the need for improved treatment strategies to prolong patient survival [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic cancer is often difficult to diagnose in an early stage; only 10-15% of patients are eligible for surgical treatment at diagnosis. Current clinical treatments for pancreatic cancer have limited efficacy, highlighting the need for improved treatment strategies to prolong patient survival (3,4). Implantation of radioactive isotopes for the treatment of pancreatic carcinoma has been used for the past several decades as it can maximize local dose and minimize irradiation of surrounding normal tissue (5 -7).…”
mentioning
confidence: 99%
“…As shown in Fig. 3, the curves described as a exponential (Ln(S(t)/S 0 ) = -k 1 t =-t/τ), indicated that terbium ions occupied the same average coordination environment [13]. The luminescence lifetimes of terbium at excited state ( 5 D 4) in the complexes were determined to be 1045.79 µs and 1172.71 µs, respectively.…”
Section: Fluorescence Spectra and Quantum Yieldsmentioning
confidence: 83%